A cross-sectional study on knowledge, attitude, and practice of using personal protective equipment among farmers using pesticides - Yaseen, Mohammed; Bhat, Waseem Hussain; Madhav, Dhruv Divesh; Krishnan, Athira; Ramaiah , Balakeshwa (International Journal Of Community Medicine And Public Health, 2024)
Background: India’s vast agricultural sector is crucial to the global economy, providing food, raw materials, and employment. However, pesticide use poses significant health risks to farmers. Pesticides, classified by the WHO based on toxicity, can accumulate in the environment, leading to long-term health issues like neurotoxicity and cancer. Despite the availability of personal protective equipment (PPE), its use is often inadequate due to gaps in knowledge, attitude, and practice. This cross-sectional study evaluated these aspects among farmers in Bangalore, India, aiming to identify deficiencies and provide recommendations to improve PPE usage, thereby enhancing farmer safety and promoting sustainable agriculture. This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding personal protective equipment (PPE) among farmers in Bangalore, India. Methods: This study involved face-to-face interviews with 213 farmers using a structured questionnaire. The main objective was to evaluate the farmers’ KAP towards pesticide use and PPE. Statistical analysis was performed using IBM SPSS Statistics software for Windows, version 22 (Armonk, NY, USA). Descriptive statistics summarized the socio-demographic characteristics of the study population, while Pearson’s correlation analyzed the relationships between knowledge, attitude, and practice regarding PPE usage. Results: Out of 213 farmers, 58.2% exhibited low knowledge of PPE, 36.6% moderate, and 5.2% high. Attitudinally, 46.5% were unconcerned, 52.6% neutral, and 0.9% concerned about PPE. Practically, 20.2% demonstrated poor PPE practices, 53.5% fair, and 26.35% good. Conclusions: The study highlights significant gaps in knowledge and practice of PPE among farmers. Educational interventions are necessary to improve PPE usage, ensuring better health and environmental safety.